Global Economic Competition in The Fields of Information and Telecommunication Technologies and Artificial Intelligence: The Case of Russia - Alexey Sergeevich KHARLANOV; Maksim Mikhailovich NOVIKOV; Petr Aleksandrovich KOSTROMIN; Andrey Aleksandrovich BOBOSHKO; Wenhao SHEN (Communications of International Proceedings, 2022)
The relevance of the article is due to the increasing role of geopolitical and economic risks associated with the global digital systems’ restructuring and the markets’ advance by major global players. Evaluation of these processes from a scientific point of view in modern research is extremely difficult due to the digital transformation’s high speed. Currently, the international competition of companies, countries and entire regions goes beyond traditional tangible goods and moves into the digital world. The international business’ transformation towards the growth of the Industry 4.0 technologies’ use: Big Data and artificial intelligence (AI), change the power balance on the world map. Moreover, information and telecommunication technologies are becoming a means not only of marketing research and consumer needs’ personification, but also a way of foreign policy influence and even military pressure in the face of increasing international tension. Practically, all modern technologies, in addition to obvious economic advantages, have a dual purpose and can be both a means of "soft power" and "hard power" in international relations. The article describes the key aspects of the Russian economy’s digitalization, discusses factors of the 5G, 6G and "digital government" technologies’ introduction to improve the population’s life quality. The historical context and the current place of digital technology’s competitiveness in Russia against the IT market leaders: China and the USA are evaluated. Conclusions are drawn about the prospects for the artificial intelligence’s development in Russia in the context of our country’s global competitiveness.
Keywords: global competition; world economy; artificial intelligence; information and telecommunication technologies; Industry 4.0